Tindak Pidana Khusus Anak; Melakukan Kekerasan terhadap Anak hingga Menyebabkan Mati: Special Crimes for Children; Committing Violence to Children, Causing Death - Augpa Aziza; Hudy Yusuf (An Nafi': Multidisciplinary Science, 2024)
Children are the most vulnerable individuals and must be protected with all efforts so that they can grow and develop safely. However, there are tragic cases where children become perpetrators of violence against other children which results in death. The aim of this research is to analyze the legal protection of children as perpetrators of crimes and to analyze the judge's considerations in giving punishment to children in Decision Number 12 of the Special Child Special Affairs Committee. The method used in this research is normative law. The results of this research show that minors cannot receive punishments like those served by adults, this is because there are still many things that will affect them because children are still entering an unstable phase which can be influenced by many factors. The judge's considerations in handing down decisions are based on juridical and non-juridical considerations.